Analysis of Literature Sociological Approaches on The Novel Stepping By J.S. Khairen Through Cultural Values - Heni Subagiharti; Rika, Rika Riwayatiningsih; Diah Syafitri Handayani; Wan Nurul Atikah Nasution (Kirana Publisher (KNPub), 2023)
The aim of this research is to find out the sociological approach to literature and to know the cultural values in the novel Mejuang by J.S Khairen. The object of this research is the novel Mejuang by J.S Khairen first published in March 2020. The research method used is descriptive qualitative which analyzes the sociology of literature approach and the meaning of cultural values. The data in this study are text excerpts in sentences found in the novel Mejuang by J.S Khairen. Data were analyzed using the Analysis Interactive model technique from Miles and Huberman (1994:12) which divided the analysis activities into several parts, namely: data reduction, data presentation, and conclusion drawing or data verification. The results of this study indicate that the cultural value contained in the novel Mejuang by J.S Khairen is knowledge that includes knowledge, namely education. Beliefs that include belief in large stones, mystical beliefs of evil spirits and beliefs in messages from ancestral spirits. Morals that include sympathizing, big-hearted, honest, full of compassion. Law that includes customary law and statutory law. Customs which include the custom of wearing Sumbanese woven cloth, traditional ceremonies, the custom of eating betel nut, traditional houses, kissing the nose, customary eldest father, horse fights, custom of Sumba Wolla Mpadu and Pasola holidays, hamayang pray to ancestral spirits.